Effects of the alpine meadow in different phenological periods on rumen fermentation and gastrointestinal tract bacteria community in grazing yak on the Qinghai-Tibetan Plateau - Tongqing Guo; Xungang Wang; Qian Zhang; Yuna Jia; Yalin Wang; Lin Wei; Na Li; Xianli Xu; Hongjin Liu; Linyong Hu; Na Zhao; Shixiao Xu (BMC Microbiology, 2024)
Abstract Background In this study, we investigated the effects of alpine meadow in different phenological periods on ruminal fermentation, serum biochemical indices, and gastrointestinal tract microbes in grazing yak on the Qinghai-Tibetan Plateau. A total of eighteen female freely grazing yaks with an average age of 3 years old and a body weight of 130 ± 19 kg were selected. According to the plant phenological periods, yaks were randomly allocated to one of three treatments: (1) regreen periods group (RP, n = 6); (2) grassy periods group (GP, n = 6); and (3) hay periods group (HP, n = 6). At the end of the experiment, the blood, rumen fluids, and rectal contents were collected to perform further analysis. Results The concentrations of total volatile fatty acid (TVFA), acetate, glucose (GLU), triglyceride (TG), cholesterol (CHO), high density lipoprotein (HDL), and low density lipoprotein (LDL) were higher in the GP group than in the HP group (P < 0.05). However, compared with the RP and GP groups, the HP group had higher concentrations of isobutyrate, isovalerate, valerate, and creatinine (CREA) (P < 0.05). The abundance of Prevotella in the rumen, and the abundances of Rikenellaceae_RC9_gut_group, Eubacterium_coprostanoligenes_group, and Prevotellaceae_UCG-004 in the gut were higher in the GP group compared with the HP group (P < 0.05). The HP had higher abundance of Eubacterium_coprostanoligenes_group in the rumen as well as the abundances of Romboutsia and Arthrobacter in the gut compared with the RP and GP groups (P < 0.05). Conclusions Based on the results of rumen fermentation, serum biochemical, differential biomarkers, and function prediction, the carbohydrate digestion of grazing yak would be higher with the alpine meadow regreen and grassy due to the gastrointestinal tract microbes. However, the risk of microbe disorders and host inflammation in grazing yak were higher with the alpine meadow wither.